2018
DOI: 10.1177/1357633x18776095
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between telehealth and face-to-face assessment of intellectual ability in children with specific learning disorder

Abstract: Introduction Access to cognitive assessments for children living remotely is limited. Telehealth represents a potential cost- and time-effective solution. A pilot study was conducted to determine the feasibility of telehealth to assess cognitive function in children with learning difficulties. Methods Thirty-three children (median age = 9 years 11 months), recruited from the New South Wales (NSW) Centre for Effective Reading, underwent assessment of intellectual ability. Comparisons were made between the intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 19 publications
1
96
0
Order By: Relevance
“…Tele-NP is a rapidly evolving practice; however, relatively limited research is available regarding standardized data for pediatric testing administered via telehealth. To date, we are aware of two published pediatric studies (Hodge et al, 2019;Waite et al, 2010) and one webinar-presented pediatric study from Harder and colleagues (Stolwyk et al, 2020). Hodge and colleagues administered and scored the Wechsler Intelligence Scale for Children -Fifth Edition (WISC-V, Wechsler, 2014) via telehealth to children located within a clinic setting and also had a secondary in-person scorer.…”
Section: Remote Tele-neuropsychological Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…Tele-NP is a rapidly evolving practice; however, relatively limited research is available regarding standardized data for pediatric testing administered via telehealth. To date, we are aware of two published pediatric studies (Hodge et al, 2019;Waite et al, 2010) and one webinar-presented pediatric study from Harder and colleagues (Stolwyk et al, 2020). Hodge and colleagues administered and scored the Wechsler Intelligence Scale for Children -Fifth Edition (WISC-V, Wechsler, 2014) via telehealth to children located within a clinic setting and also had a secondary in-person scorer.…”
Section: Remote Tele-neuropsychological Testingmentioning
confidence: 99%
“…Harder and colleagues utilized a counter-balanced design in which each participant completed a brief neuropsychological battery via a traditional in-person evaluation and a telehealth session. Published (Hodge et al, 2019;Waite et al, 2010) and presented (Stolwyk et al, 2020) pediatric studies have included some form of in-person scoring and/or management of the test session. These studies utilized standard normative data and reported that scores did not differ significantly between traditional in-person administration and nonstandard administration via telehealth (Hodge et al, 2019;Waite et al, 2010; Harder and colleagues presented in; Stolwyk et al, 2020).…”
Section: Remote Tele-neuropsychological Testingmentioning
confidence: 99%
See 3 more Smart Citations